Transport of hepcidin, an iron-regulatory peptide hormone, into retinal pigment epithelial cells via oligopeptide transporters and its relevance to iron homeostasis - Chothe, Paresh P. (2011)
Retinal pigment epithelial cells (RPE) expresses two transport systems (SOPT1 and SOPT2) for oligopeptides. Hepcidin is an iron-regulatory peptide hormone consisting of 25 amino acids. This hormone binds to ferroportin, an iron exporter expressed on the cell surface, and facilitates its degradation. Here we investigated if hepcidin is a substrate for SOPT1 and SOPT2 and if the hormone has any intracellular function in RPE. Hepcidin inhibited competitively the uptake of deltorphin II (a synthetic oligopeptide substrate for SOPT1) and DADLE (a synthetic oligopeptide substrate for SOPT2) with IC(50) values in the range of 0.4 – 1.7 μM. FITC-hepcidin was taken up into RPE, and this uptake was inhibited by deltorphin II and DADLE. The entry of FITC-hepcidin into cells was confirmed by flow cytometry. Incubation of RPE with hepcidin decreased the levels of ferroportin mRNA. This effect was not a consequence of hepcidin-induced ferroportin degradation because excessive iron accumulation in RPE, which is expected to occur in these cells as a result of ferroportin degradation, did not decrease but instead increased the levels of ferroportin mRNA. This study reveals for the first time a novel intracellular function for hepcidin other than its established cell surface action on ferroportin.